Parental vaccine hesitancy: Recent evidences support the need to implement targeted communication strategies - Cecilia Cagnotta; Nicoletta Lettera; Mirko Cardillo; Daniele Pirozzi; Daniel Catalán-Matamoros; Annalisa Capuano; Cristina Scavone (Journal of Infection and Public Health)
In 2018, Europe experienced a surge in measles cases, revealing the consequences of suboptimal immunization coverage. This trend was exacerbated by long-standing vaccine hesitancy. Parental attitudes toward childhood vaccines have increasingly shifted, influenced by ethical, religious, and safety concerns. Vaccines hesitancy has substantially increased after the Covid-19 pandemic. Using PubMed, we reviewed cross-sectional studies, published during years 2023–2024, related to parents’ vaccine hesitancy, with the aim to provide an overview of its prevalence, underlying reasons and consequences for public health. Data summarised highlight various factors contributing to vaccine hesitancy. These include socio-demographic factors, the impact of the Covid-19 pandemic, and widespread misinformation, particularly through social media. Several cross-sectional studies show that vaccine hesitancy is often linked to lower education levels, misinformation, and decreased trust in healthcare systems. The pandemic exacerbated this issue. This article underscores the need for targeted communication strategies to address vaccine hesitancy, focusing on specific populations, such as those in low-income settings or with limited access to healthcare information. It emphasizes the importance of countering misinformation to improve vaccination rates and public health outcomes.